OPTIMIZATION OF THE METHOD FOR DETERMINING PANCREATIN PROTEASE ACTIVITY USING C-PHYCOCYANIN SUBSTRATE FROM SPIRULINA PLATENSIS - Fauzan, Fitra
C-Phycocyanin (CPC), a blue pigment protein derived from Spirulina platensis, is extensively utilized across various industries, including food, pharmaceuticals, cosmetics, and others. CPC shows potential as an alternative substrate in the determination of pancreatin protease activity. Pancreatin, a complex mixture of enzymes comprising amylase, lipase, and protease, is produced from the pancreas of mammals, such as cattle and pigs. In the pharmaceutical field, pancreatin is commonly used as an oral agent for pancreatic enzyme-replacement therapy (PERT). As a drug raw material, pancreatin must adhere to quality standards as outlined in the 4th Edition of the Indonesian Pharmacopoeia. One of these parameters is the determination of protease activity, generally using casein as the substrate. Although previous studies have explored the use of CPC as a substrate, the optimal reaction conditions for pancreatin protease activity determination have not yet been fully established. Therefore, this study aims to optimize the reaction conditions -- including temperature, PEG 6000 concentration, pH, buffer concentration, and incubation time, for the accurate determination of pancreatin protease activity. The isolation of C-Phycocyanin from Spirulina platensis was achieved through a series of steps: homogenization, sonication, centrifugation, filtration, precipitation with ammonium sulfate, and the Aqueous Two-Phase System (ATPS) utilizing PEG 6000, resulting in the CPC Purification Fraction (F-ATPS). This fraction was then characterized using UV-Vis spectrophotometry and the Bradford method for protein content determination. Additionally, PEG 6000 content was analyzed using Attenuated Total Reflectance-Fourier Transform Infrared (ATR-FTIR) spectroscopy. As a result, the optimal conditions for the determination of pancreatin protease activity were identified as follows: C-Phycocyanin concentration of 130 ?g/mL, 0.05 M phosphate buffer at pH 7.2, and PEG 6000 at 5.9% (w/v), with an incubation at 37°C. These conditions are applicable for pancreatin concentrations ranging from 5 to 35 IU/mL (when mixed), with an incubation period of 10 to 30 minutes.